Impact of Public Health Insurance on Out-of-Pocket Health Expenditures of the Near-Poor in Vietnam - Nguyen Duc Thanh; Bui Thi My Anh; Phung Thanh Hung; Pham Quynh Anh; Chu Huyen Xiem (SAGE Publishing, 2021)
Out-of-pocket payment is one of the indicators measuring the achievement of Universal Health Coverage. According to the World Health Organization, for countries from the Asia Pacific Region, out-of-pocket payments should not exceed 30%-40% of total health expenditure. This study aimed to identify factors influencing out-of-pocket payment for the near-poor for outpatient healthcare services as well as across health facilities at different levels. The data of 1143 individuals using outpatient care were used for analysis. Healthcare payments were analyzed for those who sought outpatient care in the past 6 months. The Heckman selection model was used to control any bias resulting from self-selection of the insurance scheme. The finding revealed that health insurance reduces average out-of-pocket payments by about 21% ( P  < .001). Using private health facilities incurred more out-of-pocket payments than public health facilities ( P  < .001). The study suggested that health insurance for the near-poor should be modified to promote universal health coverage in Vietnam.